UJI AKTIVITAS PENGHAMBATAN ENZIM α-GLUKOSIDASE EKSTRAK ETANOL BIJI BUAH ALPUKAT SANGRAI (Persea americana Mill.) SECARA IN VITRO - St. Maryam Maryam; Asriani Suhaenah; Nurul Fadhillah Amrullah (Fakultas Farmasi UMI, 2020)
It is known that the seeds of avocado (Persea americana Mill.) are one part of the avocado widely used to treat various diseases, including diabetes. Based on the previous research, avocado seeds contain flavonoids with the potency as inhibitors of the enzyme α-glucosidase. The research aimed to determine the potency of ethanol extracted by meceration using 96% ethanol. The inhibitory activity was assayed using ELISA (Enzyme-Linked Immunosorbant Assay) reader measured at the wavelength of 405 with an acarbose comparator. The results showed that the ethanol extract of avocado seeds had an inhibitory activity included in the active category based on IC50 value of 34.300 µg/mL. Meanwhile, the acarbose had inhibition activity included in the very active category with an IC50 value of 0.253 µg/mL.